Chemical quality of red beans instant drink (Phaseolus vulgaris L.) with added red ginger (Zingiber officinale var. Rubrum) - Rahman, Suburi; Dwiani, Afe (Universitas Muhammadiyah Mataram, 2023)
Drinks in the form of powder or flour which dissolve easily in hot or cold water, do not precipitate, and are quickly and easily served are known as instant drinks. Instant drinks are made from natural ingredients, including red beans and red ginger. This study aims to determine the effect of adding red ginger to the chemical quality of instant drinks. Completely Randomized Design (CRD) was used in this study. The treatment in this study was the addition of red ginger to red bean instant drink with 5 treatments, namely M1 (100g red beans: 5g red ginger), M2 (100g red beans: 10g red ginger), M3 (100g red beans: 15g red ginger), M4 (100g red beans: 20g red ginger), and M5 (100g red beans: 25g red ginger). Each treatment was repeated 4 times to obtain 20 replicates. The research stages include: making red bean juice and red ginger juice, mixing red bean juice and red ginger juice according to the treatment for making instant drinks and evaluating the chemical quality of instant drinks. Based on the results of Analysis of Variance (ANOVA) and Honest Differential Follow-up Test (BNJ 5%), it is known that the addition of red ginger has a significant effect on the chemical quality (water content, pH and antioxidant content) of instant drinks. All chemical qualities tested met SNI standards for instant beverages with moisture content values ranging from 3.73% - 4.56%, pH between 6.52 - 6.96 and antioxidant levels between 82.66% - 94.24%.